Influencia de la ética profesional del contador público en el éxito de las empresas en la provincia de Otuzco. - Majo Juárez, Juana Deisy (2011)
This thesis is entitled: "Influence of CPA professional ethics in the business success in the provincia the Otuzco is part of the research results that had been gradually during the course of 2011, which shows how concern First of all, the need for change of qualification at the time of accounting advice to the company that provides the services, advisory services having such high degrees of abilities and skills that enable successful enterprise in the economic field without leaving the degree of commitment to society. The thesis aims of stress the need to facilitate the accounting profession studies the relationship between ethics, service quality and business success In research there are keywords such as: professional ethics, negligence, inexcusable negligence, tax crimes and a number of words related to the research topic.